2017
DOI: 10.1155/2017/6526214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Shaker Exercise on the Amplitude and Duration of Swallowing Sounds: Evidence from Cervical Auscultation

Abstract: Objective Anecdotal evidence shows that the Shaker exercise and its modifications improve pharyngeal muscle contraction. However, there is no experimental evidence for the same. Thus, the present study examined the effect of modified Shaker exercise on the amplitude and duration of pharyngeal muscle contraction using cervical auscultation. Design The study follows a cross-sectional study design, where 50 healthy individuals (23 males and 27 females) performed modified Shaker exercise and noneffortful swallow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…A similar study supported the current finding; which have been performed by Suman, Manzoor, Azmat, Ibrahim and Tahir (2015) [32] on patients with dysphagia with different causes that have been interfered against swallowing function by narrowing esophagus sphincter through compression; those patients had been trained on the swallowing exercise by the end of their study; they revealed that there was improvement in clearing food out of mouth after receiving the exercise as 95% reported that swallowing exercises worked for improvement; 85% reported wet/gurgly voice quality improved as well after exercise and no voice change after swallowing while coughing/choking decreased to be 90% had no complain. Also another recent study by Babu, Balasubramaniam and Varghese (2017) [13] found result which congruent with the recent study as their study's results revealed significant differences of swallows sound with modified Shaker Exercise when they compared to non effortful swallow.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A similar study supported the current finding; which have been performed by Suman, Manzoor, Azmat, Ibrahim and Tahir (2015) [32] on patients with dysphagia with different causes that have been interfered against swallowing function by narrowing esophagus sphincter through compression; those patients had been trained on the swallowing exercise by the end of their study; they revealed that there was improvement in clearing food out of mouth after receiving the exercise as 95% reported that swallowing exercises worked for improvement; 85% reported wet/gurgly voice quality improved as well after exercise and no voice change after swallowing while coughing/choking decreased to be 90% had no complain. Also another recent study by Babu, Balasubramaniam and Varghese (2017) [13] found result which congruent with the recent study as their study's results revealed significant differences of swallows sound with modified Shaker Exercise when they compared to non effortful swallow.…”
Section: Discussionsupporting
confidence: 81%
“…Shaker Exercises is a series of sustained and repetitive head lifting exercises to enhance the strength of suprahyoidandinfrahyoid muscular activity, reduces pyriform sinus residue and backflow aspiration and also improves swallowing functions (Babu, Balasubramaniam & Varghese, 2017) [13]. Shaker exercise includes isometric and isotonic exercises.…”
Section: Introductionmentioning
confidence: 99%
“…In the NJF-NFRP condition, the swallowing sound was recorded during resistance in the isometric contraction of the middle limb. In the Shaker-type exercise condition, the swallowing sound was recorded during isometric neck flexion 6) . In the control condition, the swallowing sound was recorded during relaxed sitting in a chair.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The Shaker exercise, a series of sustained and repetitive head lifting with isometric and isotonic tasks, is frequently used in rehabilitation for swallowing disorders to enhance suprahyoid and infrahyoid muscle strength 1,2) , resulting in improved superior-anterior movement of the hyoid and a wider upper esophageal sphincter (UES) opening [2][3][4] . Furthermore, strengthening the pharyngeal muscle activity can decrease the amount of residue in the piriform sinus and prevent aspiration 5,6) . In the Shaker exercise, the isometric tasks were performed by three repetitions of raising the head for 1 minute followed by a 1-min rest, and the isotonic tasks were performed by 30 repetitions of alternate up-and-down movement of the head.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation